Pentingnya Literasi Kesehatan Mental Bagi Generasi X - Vera Nazhira Arifin; Miftahul Jannah; Nurnarita Laila; Wardiati; Mira Gusweni (JKA, 2024)
Abstract Generation X, composed of individuals born between 1965 and 1980 facing unique challenges related to mental health The rapid technological development as well as significant socio-economic changes during this period have shaped the characteristics and patterns of this generation's behavior. Improving mental health literacy among Generation X is becoming crucial to supporting their mental well-being and helping with an ever-changing environment. This research aims to explore the importance of mental health literacy for Generation X and the strategies that can be applied to enhance it. Mental health literature includes understanding of mental well-being, identifying mental health problems, and the ability to find appropriate help.